Prevalence, Patterns and Peculiarities of Depression among Tuberculosis Patients Attending Directly Observed Treatment Short-course (DOTS) Centers in Lagos State Nigeria (American Journal of Medical Science and Innovation, 2024)
Tuberculosis (TB) is an infectious disease that is life-threatening to vulnerable populations, and has been reported to be associated with depression. Nigeria is one of the countries with a high TB burden, and with the current economic hardship in Nigeria, people are becoming poorer suggesting more TB patients are more likely to elapse into depression. The aim of this research was to assess the prevalence, patterns and peculiarities of depression among TB patients attending Directly Observed Treatment Short course (DOTS) centers in Lagos State, Nigeria. A descriptive, cross-sectional survey was conducted among 301 TB patients at 8 DOTS centers in Lagos State, Nigeria using a two-stage sampling method. Data was collected using interviewer-administered questionnaires to elicit responses from the TB patients. Patient Health Questionnaire-9 (PHQ-9) was used to determine and assess depression. Data was analyzed using SPSS version 23.0, with the Chi-square test being used to check for the association between socio-demographic characteristics and depression among the respondents. Mean age of the respondents was 35.1±11.7 years. A majority (71.8%) of the respondents were males, 69.1% were Christians, Yorubas were most (52.2%), 88.4% earned ≤N150,000 monthly, and only 1 respondent had no formal education. The prevalence rate of depression among the TB patients was 51.8%. Socio-demographic characteristics like gender (females were more affected), low financial status, and low educational level were associated with depression (p0.05). Depression among TB patients is real as one in every two TB patients is depressed. Therefore, healthcare workers at DOTS centers should pay adequate attention to signs of depression among their patients.